Theorising Indigenous health: a political economy of health and substance misuse - Saggers, S.; Gray, Dennis (2002)
For more than two decades we have bene engaged in a program of research which examines the health of Indigenous people. More recetnly this work has focussed on ways in which the substance misuse affects communities, and their responses to it. Our work is framed by understandings derived from political economy, which directs attention to the web of political and economic relations surrounding individuals and social groups. We have stressed that this framework should not be interpreted in a crudely deterministic fashion, which neglects the nuances of the social determinants of health, or individual and community agency. Much of our recent work documents such agency in community-based actions throughout Australia. In this paper we examine Indigenous drinking and its consequences, outline a political economy approach to drinking, and discuss how this has informed our work. We conclude with a discussion of some criticisms of this approach and our responses.